Image processing and intelligent computing systems - Singhal, Prateek, editor.; Abhishek Verma,; Shrivastava, Prabhat Kumar; Ranga, Virender; Kumar, Ram 261846 (Boca Raton : CRC Press)
Includes bibliographical and references